Replica placement algorithm for highly available peer-to-peer storage systems - Song, G.; Kim, S.; Seo, D. (1st International Conference on Advances in P2P Systems, AP2PS 2009, 2009)
Peer-to-peer (P2P) technology is an emerging approach to overcoming the limitations of the traditional client server architecture. However, building a highly available P2P system is quite challenging, in particular a P2P storage system. The reason is due to the fundamental nature of P2P systems: peers can join and leave at any time without any notice. Replication is one of the strategies in overcoming the unpredictable behavior of peers. A good replication algorithm should use the minimum number of replicas to provide the desired availability of data. The popular approach in the previous studies is a random placement of replicas, but it ignores the wide difference in the availability of each peer. In this paper, we develop a replica placement algorithm which exploits the availability pattern of each individual peer. By comparing our algorithm with a random placement scheme, we show that our algorithm dramatically improves the data availability with moderate overhead in terms of memory consumption and processing time in both ideal and practical conditions. ？ 2009 IEEE.